Tough, Transparent, 3D‐Printable, and Self‐Healing Poly(ethylene glycol)‐Gel (PEGgel). Issue 11 (3rd February 2022) - Wang, Zhenwu; Cui, Haijun; Liu, Modan; Grage, Stephan L.; Hoffmann, Maxi; Sedghamiz, Elaheh; Wenzel, Wolfgang; Levkin, Pavel A.
Abstract: Polymer gels, such as hydrogels, have been widely used in biomedical applications, flexible electronics, and soft machines. Polymer network design and its contribution to the performance of gels has been extensively studied. In this study, the critical influence of the solvent nature on the mechanical properties and performance of soft polymer gels is demonstrated. A polymer gel platform based on poly(ethylene glycol) (PEG) as solvent is reported (PEGgel). Compared to the corresponding hydrogel or ethylene glycol gel, the PEGgel with physically cross‐linked poly(hydroxyethyl methacrylate‐ co ‐acrylic acid) demonstrates high stretchability and toughness, rapid self‐healing, and long‐term stability. Depending on the molecular weight and fraction of PEG, the tensile strength of the PEGgels varies from 0.22 to 41.3 MPa, fracture strain from 12% to 4336%, modulus from 0.08 to 352 MPa, and toughness from 2.89 to 56.23 MJ m –3 . Finally, rapid self‐healing of the PEGgel is demonstrated and a self‐healing pneumatic actuator is fabricated by 3D‐printing. The enhanced mechanical properties of the PEGgel system may be extended to other polymer networks (both chemically and physically cross‐linked). Such a simple 3D‐printable, self‐healing, and tough soft material holds promise for broad applications in wearable electronics, soft actuators and robotics. Abstract : A novel and efficient solvent strategy is proposed to enhance and refine the performance of polymer gel with a large range via using poly(ethylene glycol) (PEG) as solvent. Due to this unique solvent system, the obtained gel exhibits long‐lasting performance (>1 month), high stretchability (6000%), rapid self‐healing (1 min), suitable for self‐healing pneumatic actuators.